Investigation of the air environment of the working areas of foundries with modern technologies for the manufacture of cores and molds - A. M. Lazarenkov; M. A. Sadokha (Литьë и металлургия)
Modern technologies for manufacturing cores and molds using cold-hardening mixtures are considered. The results of studies of the content of harmful substances in the air of the working area during the manufacture of cores and molds by various processes (NO-WAX, Alpha-set, Beta-set, COLD-BOX-AMINE, EPOXY-SO2 process, RESOL-CO2) and pouring molds and cores with liquid metal are presented. It is noted that a complex of harmful substances is fixed in the air, the composition of which depends on the processes used to obtain cores and molds, binding materials, metal poured into molds, and the nature of production. It is established that in order to ensure safe working conditions for workers in the organization of production, it is necessary to take into account the sanitary and hygienic characteristics of the substances used and the conditions of a particular production.